Agrobiological characteristics of the new ultra earlyripening winter barley variety ‘Foks 1’ - E. G. Filippov; A. A. Dontsova; D. P. Dontsov; I. M. Shapovalova (Зерновое хозяйство России, 2020)
The purpose of current work was to conduct an economic and biological estimation of the main morphobiological traits and properties of the ultra-early-ripening winter barley variety ‘Foks 1’ in comparison with the standard variety. In connection with the increasing climate aridity in recent years, the relevance of the production uses of early-ripening varieties of grain crops, including winter barley, has increased. For several decades the Federal State Budgetary Scientific Institution “Agricultural Research Center “Donskoy” has been working in this direction, which resulted in the development of the new ultra early-ripening winter barley variety ‘Foks 1’. Since 2019 the variety ‘Foks 1’ has been included in the State List of Breeding Achievements of the Russian Federation in the North Caucasus region. The variety parentage has the highly winter-resistant, lodging-resistant and large-grain varieties. The variety ‘Foks 1’ ripens on average 8–10 days earlier than the middle-ripening standard variety ‘Timofey’. On average, over the years of study in the Competitive Variety Testing (2017–2019), the trait “1000 grains weight” of the variety was 42.5 g, that of the standard variety was 40.2 g, the trait “grain nature” was 672 and 656 g/l, respectively. The trait “number of grains per head” of the new variety was 51, that of the standard variety was 45. The new variety formed an average yield of 8.1 t/ha, the excess over the standard was 0.5 t/ha. The variety ‘Foks 1’ was of a high level of winter tolerance and was resistant to lodging, it was also tolerant to damage by the main leaf diseases widespread in the region. The study results at the state variety plots of the Russian Federation and ecological testing in various soil and climatic zones have shown that the new ultra early-ripening winter barley variety ‘Foks 1’ under increasing climate aridity is undoubtedly of practical interest for cultivation in the North Caucasian region of the Russian Federation.